2007
DOI: 10.1021/jo701923z
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resolution of (±)-1,2-Bis(2-methylphenyl)ethylene-1,2-diamine as a Chiral Framework for 2-Iminoimidazolidine with 2-Methylphenyl Pendant and the Guanidine-Catalyzed Asymmetric Michael Reaction of tert-Butyl Diphenyliminoacetate and Ethyl Acrylate

Abstract: (+/-)-1,2-Bis(2-methylphenyl)ethylene-1,2-diamine, prepared from benzil and ammonium acetate, was optically resolved as a chiral framework for 2-(1-benzyl-2-hydroxyethyl)imino-1,3-dimethylimidazolidine with 2-methylphenyl pendants at the 4,5-positions. Catalysis ability of the 1,3-dimethyl-4,5-bis(2-methylphenyl)imidazolidine and the related 1,3-dibenzyl-4,5-diphenylimidazolidine was examined in the asymmetric Michael reaction of t-butyl diphenyliminoacetate and ethyl acrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…It is theoretically possible to introduce five chiral centers in the guanidine system. We found that modified guanidines prepared using our original methods [4][5][6] were effective not only in catalytic [7][8][9][10][11][12][13] but also in stoichiometric asymmetric syntheses. 14,15) The concept of modified guanidines as chiral auxiliaries in asymmetric synthesis is illustrated in Chart 2, [16][17][18] in which reactive, but resonance-stabilized, guanidinium salts 5 could be produced from guanidines 4 by quarternarization with a reagent (A-B).…”
Section: Modified Guanidines As Chiral Auxiliaries (Functionality As mentioning
confidence: 99%
See 1 more Smart Citation
“…It is theoretically possible to introduce five chiral centers in the guanidine system. We found that modified guanidines prepared using our original methods [4][5][6] were effective not only in catalytic [7][8][9][10][11][12][13] but also in stoichiometric asymmetric syntheses. 14,15) The concept of modified guanidines as chiral auxiliaries in asymmetric synthesis is illustrated in Chart 2, [16][17][18] in which reactive, but resonance-stabilized, guanidinium salts 5 could be produced from guanidines 4 by quarternarization with a reagent (A-B).…”
Section: Modified Guanidines As Chiral Auxiliaries (Functionality As mentioning
confidence: 99%
“…7,11) A 1,3-disubstituted (4S,5S)-diarylimidazolidine skeleton 23 with an (R)-1-(2-hydroxymethyl)-2-phenylethylimino moiety at the 2 position (or the enantiomer), which can be prepared using method I, was found to be the most effective catalyst in these reactions, in which an (R)-excess adduct 24 was obtained. Treatment with ethyl acrylate (22a) as a vinyl compound in the presence of catalyst 23a [designated as "(ϩ)-Chiba-G"] smoothly afforded the adduct 24a (97% ee in 85% yield) when the reaction was carried out without solvent (for 3 d), whereas a less effective reaction (79% ee in 15% yield) was observed in tetrahydrofuran (THF) solution (for 7 d).…”
Section: )mentioning
confidence: 99%
“…27 On the other hand, the synthesis of biologically active imidazolines, such as clonidine and indanazoline has been developed by Cussac et al through the condensation between primary amines and imidazolidin-2-ones or 2-methylsulfanyldihydroimidazoles. [28][29][30][31] Other procedures involve the condensation of amines with dihydroimidazol-3-ium-2-sulfonate 32 or with protected imidazolidine-2-thione, though the last procedure requires the use of mercury (II) chloride. 9 As part of our program to develop new procedures for the synthesis of heterocyclic systems, [33][34][35] we investigated several carbon-nitrogen bond forming reactions directed to the synthesis of 2-aminoimidazole derivatives.…”
Section: Figurementioning
confidence: 99%
“…For example, we managed to prepare a single crystal of the complex salt of the l-isomer of 1,2-bis(2-methylphenyl)ethylene-1,2-diamine, but not the d-isomer, using 9-(d)-camphorsulfonic acid after several trials of salt formation using tartaric acid, ammonium hexafluorophosphate, or hydrochloric acid. 19) For this purpose, advanced Marfey's method is more suitable because it has the following advantages: 1) Operations are easy; 2) Desired peaks can be definitely detected by mass spectrometry; 3) The 9A-FDLA method is e#ec-tive for identification of the isomers; and 4) The absolute configuration can be definitely determined by the elution order.…”
Section: Elution Behavior Of 12-diphenylethylene-12-diamine Derivatmentioning
confidence: 99%